Intelligence Quotient and Learning Outcomes: A Correlational Study of Guidance and Counseling Undergraduates - Endang Surtiyoni; Nurlela Nurlela; Evia Darmawani; Dendi Irawan; Prisca Putri Fatricia (Universitas Muhammadiyah Metro, 2026)
Intelligence Quotient (IQ) is widely assumed to be a primary determinant of academic success, yet preliminary observations in the Guidance and Counseling Study Program of FKIP Universitas PGRI Palembang showed that several students with superior IQ obtained lower grade point averages (GPA) than their peers in the average category. This study aimed to examine the correlation between IQ and the learning outcomes of the 2023 cohort. A quantitative correlational design was employed with total sampling of 72 students. IQ data were collected using the Culture Fair Intelligence Test (CFIT) Scale 3, and learning outcomes were obtained from students' GPA documents in the first and second semesters of the 2023/2024 academic year. Data were analyzed using normality, linearity, and homogeneity tests, Spearman's rank correlation, and simple linear regression. The results showed no statistically significant correlation between IQ and GPA (Spearman's rho = -0.078, p = 0.514; regression coefficient p = 0.271 > 0.05), with IQ accounting for only 1.7% of the variance in learning outcomes (R² = 0.017), while the remaining 98.3% was explained by other factors. These findings indicate that IQ alone does not determine students' academic achievement and imply that guidance and counseling services should also address non-cognitive factors such as motivation, learning habits, and emotional aspects to optimize student learning outcomes.